Subtherapeutic INR due to warfarin interaction with smokeless tobacco. (18th September 2020) - Nicolas, Diala; Elmouhayyar, Christopher; Nicolas, Samar; Talj, Juliana; Hattar, Laith; Alhudairy, Maad
Abstract: We report an interesting case of warfarin resistance and subtherapeutic international normalized ratio (INR) in the setting of chronic smokeless tobacco use. A 33‐year‐old white male with a mechanical mitral valve failed to achieve therapeutic INR despite being on warfarin doses of up to 30 mg by mouth daily. The patient admits to chewing tobacco daily for the past 16 years. While evaluating potential causes of subtherapeutic INR, nonadherence, drug interactions, genetic polymorphisms, and dietary factors were considered. Subtherapeutic INR may be due to increased exposure to vitamin K from chewing tobacco. Tobacco is rich in vitamin K, and its chronic use may have caused the failure to attain a therapeutic INR. To our knowledge, there is only one other case of warfarin resistance resulting from smokeless tobacco described in published literature.